2018
DOI: 10.1039/c7ra12376k
|View full text |Cite
|
Sign up to set email alerts
|

Facile construction of dual-targeting delivery system by using lipid capped polymer nanoparticles for anti-glioma therapy

Abstract: A facile and reliable platform to construct dual targeting nanoparticles for glioma treatment, and the targeting efficiency was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…This could affect the interactions between the polar heads or hydrophobic chains with the PLGA and MTM and therefore affect the final colloidal stability, size, PDI and EE. The ability of our PLGA micelles to entrap MTM (up to 87%) were higher than that reported by Wang et al for doxorubicin encapsulation (44%) using the same method with soybean lecithin as the main micelle component [ 56 ]. This method was also used by Liu et al to encapsulate MTM in poly-ethylene glycol-coated PLGA nanoparticles [ 26 ].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This could affect the interactions between the polar heads or hydrophobic chains with the PLGA and MTM and therefore affect the final colloidal stability, size, PDI and EE. The ability of our PLGA micelles to entrap MTM (up to 87%) were higher than that reported by Wang et al for doxorubicin encapsulation (44%) using the same method with soybean lecithin as the main micelle component [ 56 ]. This method was also used by Liu et al to encapsulate MTM in poly-ethylene glycol-coated PLGA nanoparticles [ 26 ].…”
Section: Discussioncontrasting
confidence: 57%
“…For the synthesis of PLGA micelles, we tested different nanoparticle formulations by modifying the main amphiphilic component of the micelle, i.e., using both non-ionic surfactant, phospholipid, or a combination of both. In addition, we also studied the effect of adding a membrane stabilizer (cholesterol) following the method (emulsion/solvent evaporation) reported by Wang et al to encapsulate doxorubicin [ 56 ]. This could affect the interactions between the polar heads or hydrophobic chains with the PLGA and MTM and therefore affect the final colloidal stability, size, PDI and EE.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry results revealed that ANG-2 decorated NPs and also Apt and ANG-2 dual decorated NPs displayed fluorescence significantly stronger than those treated with unmodified NPs. Compared to ANG-2, AS1411 reported a better-binding affinity to C6 NCLoverexpressing glioma cells 132 . The dual modification of NPs enhanced cell fluorescence, suggesting a synergistic effect of the two ligands.…”
Section: Other Types Of As1411 Aptamer-conjugated Npsmentioning
confidence: 96%
“…Proof-of-concept studies with fluorescent and confocal microscopy studies highlighted that the brain-targeted PLGA nanoparticles were able to cross the BBB and accumulated in neuronal cells, thus showing a promising brain drug delivery system.Pharmaceutics 2020, 12, 72 2 of 11 system (CNS) (by endothelial cells on the basolateral surface, neuroblasts, microglia, astrocytes, and neurons) [9][10][11][12]. This ligand has been highly sought after in its use to deliver nanomedicines to the brain because of its ability to activate transcytosis across the BBB, as well as its upregulation in human glioma cells [13][14][15]. To this end, Ang-2 has been conjugated to numerous nanocarrier types in order to improve BBB crossing, including liposomes, tandem micelles, PEG-PCL, solid lipid nanoparticles, dendrigraft poly-l lysine, and poly-amidoamine dendrimers to deliver various active compounds (Coumarin, docetaxel, siRNA, etc.)…”
mentioning
confidence: 99%
“…[20][21][22]. However, only a few studies indicated that PLGA-based nanoparticles modified with Ang-2 could be a promising active brain-targeting drug delivery system [13,14,18,23,24]. In this work, we focused on creating and characterizing targeted Ang-2 PLGA nanoparticles (NPs); the surface was engineered by conjugating Ang-2 directly to the polymer, and nanoformulation was then gained, or with post-formulation anchorage to NP through the conjugation of the thiol-containing cysteine added to the Ang-2 and a maleimide containing PLGA.…”
mentioning
confidence: 99%